Soviet postage stamp commemorating 1965 IUPAC meeting in Moscow (1965)
Stamp issued to publicize the 20th Congress of the International Union of Pure and Applied Chemistry (IUPAC), held in Moscow, July 12-18. The names of both the organization and the host city are spelled with chemical symbols. In addition, the stamp shows a molecular diagram of an unidentified substance and uses a retort as a background. The ink used for the globe diagram and the face value of the stamp (4 kopecs) are fluorescent.
Keywords: Postage stamps; Chemistry; International Union of Pure and Applied Chemistry; Soviet Union; Science on postage stamps